STRATEGI MANAJEMEN VIAVIA TOUR AND TRAVEL YOGYAKARTA DALAM MEWUJUDKAN RESPONSIBLE TOURISM - , HANIK ([Yogyakarta] : Universitas Gadjah Mada, 2014)
At the moment tourism already having a change of views on activity tourism. Currently tourists began prefer to arrages trips their own. Tourist want to enjoy the ride without bound to limits time when they enjoy their way. Tourist have a desire to know a place that is visited by many more in, not only function as enjoying the sun, sea and sand. With we change the trend in tourism when these appear alternative tourism, sustainable tourism, and responsible tourism, that is the development of sustainable tourism. The existence of alternative tourism give positive impact to the natural environment, social and cultural. One of the tour and travel who organizes alternative tourism an alternative to the concept of responsible tourism based on sustainable tourism is ViaVia tour and travel Yogyakarta. The study aims to would like to know the importance of the responsible tourism from ViaVia tour and travel Yogyakarta and responsible program purposes of tourism. Other purposes of this research is analyzing strategy management ViaVia tour and travel Yogyakarta in implementing the responsible tourism. In addition to this writer using the method of qualitative data obtained based on the results of observation, interview, partisipasif, literature review and analyze with SWOT analysis to strengthen the research results in ViaVia tour and travel. In the realization of responsible tourism ViaVia organizes an alternative tour, where the tourist in the tour are invited to enjoy, see Yogyakarta from different viewpoints and interact and work directly with the local population. In addition to this, to go to the places to be visited, used bicycles, ViaVia walk also means publictransport, cooperate with Trees4Trees in the use of motor vehicles to reduce pollution from the impact of tourism activities. Furthermore, in practice there are some barriers experienced by ViaVia tour and travel Yogyakarta, by it from internal and external, including the availability of the guide as well as a tour and travel to another the tour organized by ViaVia tour and travel.